Market Day Program for Low Class: Improving Independent Character Education at Elementary School - Oktaviana Saputri; Sukartono (Universitas Pendidikan Ganesha, 2023)
One of the central issues currently being discussed in the world of education is character education. Character education is experiencing disorientation, the fading of Pancasila values, and the shifting of life values as a result of globalization. This means that character education needs to be instilled from an early age, especially in elementary schools, one of which is independent character education. The aims of this study are to analyze the implementation of strengthening independent character education through